Optimasi pengoperasian pintu tol. - Perpustakaan UGM, i-lib ([Yogyakarta] : Fakultas Kehutanan Universitas Gajah Mada, 1999)
ABSTRAK The tollroad must give the higher service to the traffic than alternative roads. Vehicles will enter the queueing system if pass the toll gates. This investigation taken at Pondok Gede East Toll Plaza at Jakarta-Cikampek Tollroad that has 6 entrances gates (take ticket only) and 11 gates for payment toll fee. The intention of the research is to optimize the opening of the toll gates which are appropriate to the traffic arrival. The investigation concerns with the service time at toll gates taken at entrance gates and payment toll fee gates with or without change money or (customer). The service time began from the time that the vehicle moves forward being served until the vehicle left the toll gate. The results showed that the rate of service time is 8,74 seconds per vehicle for the payment toll gate with change money, and 5,62 seconds per vehicle for the payment toll gate without change money (customer), and 4,06 second per vehicle for the entrance gate. The use of equations of the queueing system, and the arrival vehicles are simulated, the average number of the vehicles waiting to be served and average waiting time could be counted. Considering the maximum waiting time and number of vehicles waiting that could be tolerated, the number of toll gates must be opened appropriate to the traffic arrival could be fixed on. The conclusion of this investigation suggested that for the entrance toll gate serve 13 up to 14 vehicles per minute per gate and 5 up to 6 vehicles per minute per gate for the payment toll gate with change money. Key word: pintu tol, stokastik, palayanan pintu tol